Automation of Library Services—Turning Point in Development of Academic Libraries - Viktoriya Ivanova (Engineering proceedings, 2024)
Automation and the use of information technology and are the first steps towards fast and huge change in every organization; they lead to the development of new services, the restructuring of units, and the implementation of different management strategies according to specific characteristics. Universities and their libraries have taken an active role in this transformation. Automation and innovations serve as turning points in the development of academic libraries, as they improve the process of acquiring, storing, processing, retrieving, and delivering information.